Prevalence of Dyslipidemia among Type 2 Diabetes Mellitus Patient in Combined Military Hospital, Sylhet - Mostofa, Md Golam; Ferdous, Nur E Jannatul; Bhuiyan, Mohammad Abdul Quddus (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: Diabetes mellitus is a group of metabolic disorders that are caused by deficiency of insulin secretion or decreased ability of insulin to act effectively on target tissues, particularly muscle, liver and fat. Diabetes is associated with high risk of cardiovascular diseases and underlying lipid abnormalities. Its early identification can make aggressive cardiovascular preventive management possible. Objectives: To determine the prevalence and pattern of lipid abnormalities in type 2 diabetes mellitus. Methods: A Retrospective, descriptive cross-sectional study was conducted in Combined Military Hospital, Sylhet, Bangladesh over a period of 2 years from January 2018 to December 2019. Diagnosed patients of type 2 diabetes mellitus of different age group and both sex were selected for this study according to inclusion and exclusion criteria. The lipid profiles and fasting blood sugar values of 85 known diabetics were studied. Their serum samples were assessed for fasting blood glucose (FBG), total cholesterol (TC), triacylglycerol (TG), low density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol (HDL-C) by using standard biochemical methods. Results: Present study comprised of 85 diagnosed patients of type 2 diabetes mellitus. Out of those 78.8% were male and 21.2% were female. The age range was from 26 to 85 years with an average of 50.4±13.9 years. The average fasting blood glucose was noted as 10.787±4.2053mmol/l. The average total cholesterol, triglycerides, LDL and HDL were 194.35±177.07mg/dl, 226.18±115.19mg/dl, 91.08±26.79mg/dl and 39.75±9.51 mg/dl respectively. The prevalence of dyslipidemia in the present study was found as 81.2%, 14.1% were having hypercholesterolemia, 65.88% patients were having hypertriglyceridemia, 25.88% patients were having increased LDL levels and 43.52% patients were having reduced HDL levels. In respect of pattern of dyslipidemia, we found isolated and combined dyslipidemia. Conclusion: In the diabetics higher frequencies of high TC, high TG and high LDL-C levels were noted indicating diabetic patients were more prone for dyslipidemia which may lead to cardiovascular disorders. JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 3-6